PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING DALAM MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA ABULYATAMA ACEH BESAR - Putri Amalina; Syarifahrahmiza Muzana; Hasbullah; Nurul Azmi (Jurnal Pendidikan Nusantara, 2025)
This study aims to describe the effectiveness of implementing the Snowball Throwing learning model in improving the learning outcomes and critical thinking skills of students at Abulyatama High School in Aceh Besar. This study was conducted using the Classroom Action Research (CAR) method, which consisted of two cycles, each covering the stages of planning, implementation, observation, and reflection. The research subjects consisted of 30 students in grade XI. Data were collected through learning outcome tests, learning activity observation sheets, and critical thinking skills assessment rubrics. The results showed a significant increase in student learning outcomes from cycle I to cycle II, along with an improvement in their ability to analyse information, provide logical reasons, and draw conclusions based on evidence. The Snowball Throwing model proved to be capable of creating a more active, interactive, and collaborative learning atmosphere, thereby encouraging students to be directly involved in the learning process. Thus, the application of this model is highly recommended as an effective learning strategy to improve the quality of the learning process and outcomes of students. The purpose of this study was to analyse the application of the Snowball Throwing learning model in improving the learning outcomes and critical thinking skills of students at Abulyatama High School in Aceh Besar. The research method used was Classroom Action Research (CAR) with two cycles. The research subjects were 30 students in grade XI. The research instruments included learning outcome tests, observation sheets, and critical thinking skills assessment guidelines. The results showed a significant increase in both learning outcomes and critical thinking skills after the implementation of the Snowball Throwing learning model. This model proved to be effective in increasing student participation, training questioning skills, and encouraging students to think analytically and evaluatively about the material being studied.